Bacterial and archaeal community structure in the surface microlayer of high mountain lakes examined under two atmospheric aerosol loading scenarios. Issue 2 (24th January 2013) - Vila‐Costa, Maria; Barberan, Albert; Auguet, Jean‐Christophe; Sharma, Shalabh; Moran, Mary Ann; Casamayor, Emilio O.
Abstract: Bacteria and Archaea of the air–water surface microlayer (neuston) and plankton from three high mountain lakes (Limnological Observatory of the Pyrenees, Spain) were analysed by 16S rRNA gene 454 pyrosequencing (V6 region) in two dates with different atmospheric aerosol loading conditions: (1) under a Saharan dust plume driven by southern winds; and (2) under northern winds with oceanic influence. In general, bacterial communities were richer than archaea, with estimated total richness of c . 2500 OTUs for Bacteria and c . 900 OTUs for Archaea equivalent to a sequencing effort of c . 250 000 and c . 20 000 sequences, respectively. The dominant bacterial OTU was affiliated to Actinobacteria. Archaea were one to two orders of magnitude less abundant than bacteria but were more evenly distributed. Apparently, Bacteroidetes and Thaumarchaeota sequences were preferentially found at the neuston, but no consistent pattern in either total microbial abundance or richness was found in any sample. However, we observed more marked changes in microbial relative abundances between neuston and plankton in the dust‐influenced scenario. Higher community dissimilarities between neuston and plankton were also found during the Saharan dust episode, and such differences were higher for Bacteria than for Archaea. Nonetheless, relatively few (< 0.05%) of the neuston sequences matched previously identified airborne microorganisms, and none became important in the dates analysed.